Total and Cause-Specific Mortality of U.S. Nurses Working Rotating Night Shifts - Gu, Fangyi (Am J Prev Med, 2015)
BACKGROUND: Rotating night shift work imposes circadian strain and is linked to the risk of several chronic diseases. PURPOSE: To examine associations between rotating night shift work and all-cause, cardiovascular disease (CVD), and cancer mortality in a prospective cohort study of 74,862 registered U.S. nurses from the Nurses’ Health Study. METHODS: Lifetime rotating night shift work (defined as ≥3 nights/month) information was collected in 1988. During 22 years (1988–2010) of follow-up, 14,181 deaths were documented, including 3,062 CVD and 5,413 cancer deaths. Cox proportional hazards models (2013) estimated multivariable-adjusted hazard ratios (HRs) and 95% CIs. RESULTS: All-cause and CVD mortality were significantly increased among women with ≥5 years of rotating night shift work, compared to women who never worked night shifts. Specifically, for women with 6–14 and ≥15 years of rotating night shift work, the HRs were 1.11 (95% CI=1.06, 1.17) and 1.11 (95% CI=1.05, 1.18) for all-cause mortality and 1.19 (95% CI=1.07, 1.33) and 1.23 (95% CI=1.09, 1.38) for CVD mortality. There was no association between rotating night shift work and all-cancer mortality (HR(≥15years)=1.08, 95% CI=0.89, 1.19) or any other cancer, with the exception of lung cancer (HR(≥15years)=1.25, 95% CI=1.04, 1.51). CONCLUSIONS: Women working rotating night shifts for ≥5 five years have a modest increase in all-cause and CVD mortality; those working ≥15 years of rotating night shift work have a modest increase in lung cancer mortality. These results add to prior evidence of a potentially detrimental effect of rotating night shift work on health and longevity.